Clinical characteristics of patients with non-alcoholic fatty liver disease (NAFLD) in Germany – First data from the German NAFLD-Registry - Geier, Andreas; Rau, Monika; Pathil-Warth, Anita; von der Ohe, Manfred; Schattenberg, Jörn; Dikopoulos, Nektarios; Stein, Kerstin; Serfert, Yvonne; Berg, Thomas; Buggisch, Peter; Demir, Münevver; Roeb, Elke; Wiebner, Bianka; Wedemeyer, Heiner; Zeuzem, Stefan; Hofmann, Wolf P. (Zeitschrift für Gastroenterologie, 2023)
Background Non-alcoholic fatty liver disease (NAFLD) affects more than 18 million individuals in Germany. Real-world data help to better characterize the natural history of disease and standard of care.Methods The German NAFLD-Registry is a prospective non-interventional study initiated by the German Liver Foundation and aims to describe clinical characteristics and observe outcomes in patients with NAFLD recruited in secondary and tertiary care.Results From this ongoing study, baseline data of the first 501 patients (mean age 54 years, 48% women) were analysed. 13 % of the study population had a high risk for advanced fibrosis (FIB-4 ≥2.67), approximately one-third had a liver stiffness value ≥9.6kPa measured by transient elastography, and the clinical diagnosis of liver cirrhosis was present in 10%. Typical comorbidities were more prevalent in high risk as compared to low risk patients (FIB-4 <1.3) including arterial hypertension (85 vs. 42%), hypercholesterolemia (39 vs. 16%), and type 2 diabetes mellitus (T2DM) (69 vs. 26%). Patients with T2DM (192/501) had a higher NAFLD disease burden as shown by liver stiffness values ≥9.6 kPa (51%) and clinical diagnosis of cirrhosis (20%). Statins were used in 22% of the main population, while in diabetic patients, metformin, GLP-1 agonists, and SGLT2 inhibitors were used in 65, 17, and 17%, respectively. Uptake of life-style interventions such as physical exercise or nutritional counselling was generally low.Conclusion First data of the German NAFLD registry show that approximately every 10th patient has advanced NAFLD, highlights T2DM patients as a high-risk group and gives insights in the use of comedication and life-style interventions in secondary and tertiary care.
Keywords: Typ 2 Diabetes mellitus; Leberzirrhose; metabolisches Syndrom; Adipositas; NAFLD; NASH